Gender and the political economy of land in Africa - Kouamé, Euphrasie B.H.; Fofona, Namizata B. (United Nations University Institute for Natural Resources in Africa, 2015)
Evidence shows that secure land rights have positive effects on poor people in general and women in particular, especially where households previously had little security. Several countries in Africa have been undertaking land reform initiatives that prohibit gender-based discrimination; however, the results revealed a substantial gap between the development of laws and their effective implementation. This paper draws attention to the political systems within which land tenure and property rights operate, especially for women. It also points out the main challenges in securing women’s land rights in Africa and highlights the economic, social and environmental benefits of increasing women’s access to land. The analysis shows that although many of the changes in policy and law appear to be legal and technical, access to and control over land is in practice related to socio-economic characteristics and governed by cultural practices and power relations at the family, community and country levels. The paper therefore recognizes the need for innovative approaches that go beyond property rights in operationalising strategies that strengthen women’s access to land. It is not enough for land legislation to be gender-sensitive; it must be gender-transformational. Land markets could potentially contribute to this transformation but their role is still limited by poor institutional capacity. The roles that different actors (women, men, women’s organizations, community leaders, donors) can play would be crucial in the process of securing women’s access to land in Africa.
ISBN: 9789988633066
Keywords: 2000 à aujourd'hui; 2010-2019; OFDIG; afrique; approches et analyses; femmes*; genre; identités LGBTQIA2+; politique; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; thématiques; égalité des sexes

Language and masculinities: performances, intersections, dislocations - Milan, Tommaso M. (Routledge, 2015)
This volume showcases cutting-edge research in the linguistic and discursive study of masculinities, comprising the first significant edited collection on language and masculinities since Johnson and Meinhof’s 1997 volume. Overall, the chapters are linked together by a critical analytical perspective that seeks to understand the relationships between discourse, masculinities, and power. Whereas some of the chapters offer detailed, linguistically informed critiques of the ways in which old and new expressions of masculinities are complicit in the reproduction of men’s hegemonic positions of power, others provide a more complex picture, one in which collusion and subversion go hand in hand. Contributions argue for the need for research on language and masculinities to expand its remit so as to engage with "gay masculinities," and unsettle gendered categories in order to consider the ways in which women, transgender, and intersex individuals also perform a variety of masculinities. Finally, unlike Johnson and Meinhof’s 1997 collection, this volume not only offers a wider—and perhaps "queerer" perspective—on the study of language and masculinities, but also covers a broader geographical and socio-cultural spectrum, including work on Brazil, Israel, New Zealand, Singapore, and South Africa.
Donné en lecture au cours LIN2685, Jones, Lucy. Masculinity in Lesbian Discourse, the Case of 'Butch' vs 'Femme', p 174-196.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; langage; lin2685; linguistique; masculinité; premier cycle; queer; rapports sociaux de sexe; ressource en ligne; sciences humaines; sociolinguistique; sofia; thématiques; études de genres